Corporate Responsibility Towards Employees Welfare - Ilham Abbas; Salle Salle; Hardianto Djanggih (Yuridika, 2019)
Essentially, in carrying out its business activities every company is certainly cannot be separated   from responsibility, as responsibility is one of the obligations of the business actor towards consumers, employees and the surrounding environment. Responsibility also means doing something as an embodiment of awareness of obligations. In this study will analyze the company’s responsibility for employee welfare and the efforts made by the Company to improve employee welfare at PT. Semeru Ratu Jaya Makassar. The results of the study are expected to contribute thought to business actors in spreading their business activities, because employee welfare is very urgent and fundamental for employees. This is in accordance with what is mandated in Pancasila as the source of all sources of law in Indonesia and this is reflected in the 1945 Constitution of the Republic of Indonesia, precisely in the opening of the 1945 Constitution in paragraph 4 (four) concerning the national goal of promoting general welfare.